Processamento de gelatina de maracujá amarelo (passiflora edulis) enriquecida com microcápsulas de gengibre (Zingiber officinali) obtidas pelo processo de gelificação iônica - Soares, Fabiana Melo (2019)
Nowadays, consumers are more questioning about food, requiring better texture, taste, quality products and functionality. Therefore, the food industry has been working on the physical-chemical and food properties of food. Gelatine is a nutritionally rich, protein source, with low calorie content and fats, and can be used in the generation of new products. Studies have reported that passion fruit (Passiflora edulis) has bioactive compounds beneficial to health, as well as ginger, with antioxidant and anti-inflammatory properties of 6-gingerol and 6- shagaol. In this way, an incorporation of bioactive compounds into foods and beverages has attracted consumers, resulting in a great interest and interest to meet the new demands. However, most of the bioactive compounds are unstable, not always bioavailable or have undesirable taste limiting their application in food. Ionic gelling is an efficient microencapsulation technique for inserting compounds into foods for the purpose of creating a protective barrier and most nutritional foods. This context is the incorporation of bioactive compounds in foods has been growing, are sought in the demand of new consumers for products. Thus, the study was developed based on the passion fruit yellow gelatin (Passiflora edulis) with microcapsules of ginger (Zingiber officinali), in its physical, chemical, antioxidant, microbiological and sensorial properties. PH, acidity, soluble solids (° Brix), ascorbic acid, total carotenoids, total phenols, antioxidant capacity (FRAP, DPPH, ABTS), color, microbiological, microscopic analysis and analysis sensory. The translations were defended in triplicate, with the results expressed as mean ± standard deviation. Differences were isolated when p <0.05, using the Student software through the Sisvar software. As for the intake of vitamin C (11.35- 5.7 mg / 100g), protein (2.83-3.45g), pH (3.29-3.39), acidity (115-1.27g citric acid / 100 g). Phenolic preparation tips (24.41-32.94μg EAG / g), carotenoids (157-392,23 mg / g), gingerose (μg / mL Ginger Extract) and capacity antioxidant. DPPH (1.87-2.15 mmolET / g), ABTS (7.26- 8.00 mmol ET / g), FRAP (9.43-10.24 mmolET / g). Microbiological tests were not found in the presence of coliforms at 45ºC, coagulase positive staphylococci, salmonella, molds and yeasts. Regarding the sensory parameters, the most appreciated attributes were aroma, color, appearance and texture. In this way, a product with nutritional, sensorial and microbiological quality, consumption of dyes, sugars and proteins of good quality was obtained.